A qualitative study to explore the experiences of first contact physiotherapy practitioners in the NHS and their experiences of their first contact role. (December 2020) - Greenhalgh, S.; Selfe, J.; Yeowell, G.
Abstract: Purpose: First Contact Practitioner (FCP) roles have been developed for health professionals with advanced practice skills to take on many of the musculoskeletal responsibilities currently carried out by general practitioners. FCP roles are new and still developing. Currently there is little research that has investigated the experiences of FCPs. This knowledge could help stakeholders and other clinicians gain an understanding into what makes a successful FCP role. The aim of this research was to explore the experiences of FCP working in North West England to gain insight into the first point of contact service, and their experiences of this developing full time FCP role. Methods: A qualitative design using in-depth semi-structured, face-to-face interviews was undertaken to explore the experiences of FCP providing a first point of contact service. The study took place in an economically deprived and ethnically diverse location in North West England. Findings: Ten FCPs were recruited, four were appointed from Band 6 posts to FCP training posts, 9 were male. The mean years qualified was 12.8. Five themes were identified: 1. 'It's the level of clinical complexity that you're dealing with', 2. FCP role – rewards and challenges, 3. Own wellbeing, 4. Professional development and education, 5. Realities of working in practice governed by business. Conclusion: FCP roles are an exciting development for people with MSK conditions, the physiotherapy profession, primary care providers and MSK physiotherapists. Mentorship support, workload and standards of training and practice are important when considering future expansion for the sustainability of these roles. Highlights: First Contact Practitioners considered the role a positive development. Mentorship support was considered by all participants as being important. They were less confident in managing non-musculoskeletal conditions. Consistency in the number of patients seen and sessions undertaken was recommended. Standards of training and practice for training posts should be developed.